The pro-metastatic role of bone marrow-derived cells: a focus on MSCs and regulatory T cells - Koh, Bong Ihn (Nature Publishing Group, 2012)
Several bone marrow-derived cells have been shown to promote tumour growth and progression. These cells can home to the primary tumour and become active components of the tumour microenvironment. Recent studies have also identified bone marrow-derived cells—such as mesenchymal stem cells and regulatory T cells—as contributors to cancer metastasis. The innate versatility of these cells provides diverse functional aid to promote malignancy, ranging from structural support to signal-mediated suppression of the host immune response. Here, we review the role of mesenchymal stem cells and regulatory T cells in cancer metastasis. A better understanding of the bipolar nature of these bone marrow-derived cells in physiological and malignant contexts could pave the way for new therapeutics against metastatic disease.